Meta-Analysis of Spinal Anesthesia Versus General Anesthesia During Laparoscopic Total Extraperitoneal Repair of Inguinal Hernia. Issue 4 (August 2020) - Hajibandeh, Shahin; Hajibandeh, Shahab; Mobarak, Shahd; Bhattacharya, Pratik; Mobarak, Dham; Satyadas, Thomas
Abstract : Objectives: To evaluate comparative outcomes of spinal anesthesia (SA) and general anesthesia (GA) during laparoscopic total extraperitoneal (TEP) repair of inguinal hernia. Methods: We systematically searched MEDLINE, EMBASE, CINAHL, CENTRAL, the World Health Organization International Clinical Trials Registry, ClinicalTrials.gov, ISRCTN Register, and bibliographic reference lists. We applied a combination of free text and controlled vocabulary search adapted to thesaurus headings, search operators and limits in each of the above databases. Postoperative pain assessed by visual analogue scale (VAS), individual and overall perioperative morbidity, procedure time and time taken to normal activities, were the outcome parameters. Combined overall effect sizes were calculated using fixed-effect or random-effects models. Results: We identified 5 comparative studies reporting a total of 1518 patients (2134 hernia) evaluating outcomes of laparoscopic TEP inguinal hernia repair under SA (n=1277 patients, 1877 hernia) or GA (n=241 patients, 257 hernia). SA was associated with significantly lower post-operative pain assessed by VAS at 12 hours [mean difference (MD): −0.32; 95% confidence interval (CI), −0.45 to −0.20; P <0.0001] and shorter time to normal activities (MD: −0.30; 95% CI, −0.48 to −0.11; P =0.002) compared with GA. However, it significantly increased risk of urinary retention [odds ratio (OR): 4.02; 95% CI, 1.32-12.24; P =0.01], hypotension (OR: 3.97; 95% CI, 1.57-10.39; P =0.004), headache (OR: 7.65; 95% CI, 1.98-29.48, P =0.003), and procedure time (MD: 3.82; 95% CI, 1.22-6.42; P =0.004). There was no significant difference in VAS at 24 hours (MD: 0.06; 95% CI, −0.06 to 0.17; P =0.34), seroma (OR: 1.54; 95% CI, 0.73-3.26; P =0.26), wound infection (OR: 1.03; 95% CI, 0.45-2.37; P =0.94), and vomiting (OR: 0.84; 95% CI, 0.39-1.83; P =0.66) between the 2 groups. There was a nonsignificant decrease in overall morbidity in favor of GA (OR: 1.84; 95% CI, 0.77-4.40; P =0.17) which became significant following sensitivity analysis (OR: 2.59; 95% CI, 1.23-5.49; P =0.01). Conclusions: Although TEP inguinal hernia repair under SA may reduce pain in early postoperative period, it seems to be associated with increased postoperative morbidity and longer procedure time. It may be an appropriate anesthetic modality in selected patients who are considered high risk for GA. Higher level of evidence is needed. Abstract : Supplemental Digital Content is available in the text.